THE INFLUENCE OF CUSTOMER TESTIMONIALS AND ADVERTISING ON COSMETIC PRODUCT PURCHASING DECISIONS - Maulana Farhan (Lentera Barasaki Publishing House, 2023)
This study discusses the importance of customer testimonials and advertising as a forum to support STIE IBMT Surabaya students in determining purchasing decisions for a product. The purpose of this study was to determine the effect of testimonials on purchasing decisions, measure the effect of product advertising on purchasing decisions, measure the effect of customer testimonials and advertising on consumer purchasing decisions In this study, the sampling technique used simple random sampling technique. The sample in this study were students at STIE IBMT Surabaya. Data analysis techniques using multiple linear regression analysis From the above analysis it can be concluded that testimonials have a significant effect on student purchasing decisions, which is indicated by the partial test results of customer testimonials and advertising have significant effect to purchasing decisions.